Why Websites Work: An Examination of Interdisciplinary Agricultural Center Websites - Ashley N McLeod; Valerie McKee; Savannah Woodall; Brandon McKee; Joy Rumble (Journal of Applied Communications, 2018)
This study examined the online content of interdisciplinary agricultural center webpages. Content modification dates, mission statements, and content were determined through a content analysis. Many of the websites did not mention a modification date for the content, while many websites had outdated content mostly older than six months. More than two-thirds of the websites provided PDFs that visitor could download to learn more about topics, by many of the websites lacked any media element that was being coded. Additionally, many websites did not use multiple forms of media. More than half of the websites were coded as lacking any social media content or plugins, but out of the websites that did include social media content, Facebook was the most prevalent. The commonalities between the center’s mission displayed on the website and the content theme were analyzed and chi-square tests provided the degree of association. A significant association existed and an alignment between communication strategies and missions of the centers was concluded, which is important when organizations communicate about agricultural science as indicated by previous literature. It is recommended that centers communicate via their websites in a timely manner and allow modification times to be seen to viewers to show their information is up-to-date. Website media content should also be diversified and communicators of these centers should explore the unique communication opportunities provided by social media. Future research should explore the target audience of interdisciplinary agricultural centers and should analyze the messages centers are using to communicate with those audiences.
Keywords: Content Analysis; Excellence Theory; Interdisciplinary Agricultural Center; Online Media; Website Analysis